Clinical and dermatoscopic features of temporal triangular alopecia in infants. Issue 3 (2nd March 2023) - Guan, Zhiwei; Shi, Weijie; Ren, Min; Bi, Tiantian; Su, Haihui
Abstract: Objective: To summarize the clinical and dermatoscopic features of temporal triangular alopecia in infants and explore the clinical significance of dermatoscopy in the diagnosis of triangular alopecia temporalis in infants. Methods: A retrospective analysis was performed on 20 children with temporal triangular alopecia diagnosed in the dermatology clinic of Tianjin Children's Hospital from January 2015 to December 2021. Dermatoscopy was performed on all children, and images were collected. Results: The clinical features of 20 children were 15 males and five females, all of which were born immediately after birth; There were eight cases (40%) in the left temporal region, 10 cases (50%) in the right temporal region, one case (5%) in the head region, and one case (5%) in the occipital region; 19 cases were single (95%), one case was multiple (5%); There were 21 skin lesions, 15 triangular lesions (71.4%), four quasi‐circular lesions (19%), and two lance‐shaped lesions (9.5%). Trichoscopic features: The hair follicle opening in all skin lesions is normal, and the hair follicle opening can be seen with fluffy hair (vellus hair). The vellus hair is evenly distributed, and the length is diverse (both short and long vellus hair exist in the same hair loss area). There are 14 cases of white vellus hair (70%), five cases of white spots (25%), one case of honeycomb pigment pattern (5%), and one case of vascular dilation pattern (5%). Conclusion: Temporal triangular alopecia in infants has typical clinical and dermatoscopic characteristics, and the dermatoscopy can provide clinical basis for its diagnosis and differential diagnosis.